Monopolistic Competition? The Rise of Brand-Chain Competition and Unresolved Social Questions - Sumner, Glenna (Advances in Social Sciences Research Journal, 2018)
Imperfect competition in microeconomics has been known as “Monopolistic Competition” since the near simultaneous release of books by Joan Robinson and Edward H. Chamberlain in 1933. The topic is still taught in economics texts and classrooms to this day, despite little evidence that it now exists in the industrialized world. Oligopolies have moved into this highly competitive field via Brand-Chain Competition. In Brand-Chain Competition, the Oligopoly uses its deep pockets to fund research and development of new products which are sold through brand-names. While the high barriers to entry remain, and the Oligopoly faces little competition from additional firm entry into the industry, entry into a particular product market is rather simple, and highly competitive. Robinson and Chamberlain were correct that economic profits only occur in the short-run due to this high competition. They were incorrect on who the end-game players would be. Rather than massive numbers of sellers, there are massive numbers of brands and few parent corporations. These firms send out a new products via brands, with the intent to earn excess profits only until the competition can produce and market a similar product, which reduces demand for the original firm’s product in the long-run. The brand then responds by releasing a new or improved product from its chain of products, and the short-run begins again. These changes are so new, the social impacts are still a question.